If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + 6) + -3(2x + -7) = 127 Reorder the terms: 8(6 + x) + -3(2x + -7) = 127 (6 * 8 + x * 8) + -3(2x + -7) = 127 (48 + 8x) + -3(2x + -7) = 127 Reorder the terms: 48 + 8x + -3(-7 + 2x) = 127 48 + 8x + (-7 * -3 + 2x * -3) = 127 48 + 8x + (21 + -6x) = 127 Reorder the terms: 48 + 21 + 8x + -6x = 127 Combine like terms: 48 + 21 = 69 69 + 8x + -6x = 127 Combine like terms: 8x + -6x = 2x 69 + 2x = 127 Solving 69 + 2x = 127 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-69' to each side of the equation. 69 + -69 + 2x = 127 + -69 Combine like terms: 69 + -69 = 0 0 + 2x = 127 + -69 2x = 127 + -69 Combine like terms: 127 + -69 = 58 2x = 58 Divide each side by '2'. x = 29 Simplifying x = 29
| 1=d/10-12 | | 24v^2-9v+32v-12=0 | | 5y=-2.8 | | 7n-1=9+10n-12 | | 3x^2+2x-5=2x^2-2 | | 0.5=-8 | | 0.36(6)+0.04x=0.12(18+x) | | 4(6a-16)+2(2a+12)=4 | | 0.41x=8.2 | | -3(3y+v)+6(4v-4y)= | | 24-4(7-2t)=4(t-1) | | 950=25h+40 | | 1/2=-8 | | c=25h+40 | | -(2x+5)-9x= | | -x-2y=8 | | 3*32*3+u=(3*3*3-3*8)(2)+u | | 8(3x-6)=2(12x+4) | | -(4u-6)-u= | | 8x-3(3x+2)= | | 2x^2+22=0 | | 7(x-7)+16= | | 92=6(x-70)+50 | | 2x^4-x^3-x^2=0 | | x^2+y^2-4x-6y+4=0 | | 2y-2=6y+2 | | -2(-y-2)-x= | | 6x^2+7x-3=y | | .2+.2x=.4 | | 12x^2+82x-14=0 | | 3(1+d)+-5=3d+-2 | | 3x^2-35x-5=0 |